Enantioselectivity in transplacental transfer of perfluoro-1-methylheptanesulfonate (1m-PFOS): Human biomonitoring and in silico study. (June 2020) - Zhao, Lu; Chen, Fangfang; Yin, Shanshan; Xie, Jingqian; Aamir, Muhammad; Liu, Shuren; Liu, Weiping
Abstract: Perfluorooctane sulfonates (PFOS) are one of the most prominent perfluoroalkyl contaminants in humans and wildlife. Currently, information regarding enantiomer-specific exposure to PFOS in humans through transplacental transfer is lacking. This study examined 32 matched maternal serum, cord serum and placenta samples collected from mother-infant pairs in Wuhan, China. The enantiomer fraction (EF) value of perfluoro-1-methylhptanesulfonate (1 m -PFOS) was lower in cord sera (0.362 ± 0.062, n = 23) compared to maternal sera (0.422 ± 0.048, n = 21) and placenta (0.410 ± 0.060, n = 16). Evaluations of the difference between EF1 m -PFOS suggested enantioselective transplacental transfer of 1 m -PFOS. In silico evaluation of the binding affinity of 1 m -PFOS to human serum albumin (HSA) showed that the two 1 m -PFOS enantiomers enantioselectively interacted with the HSA. This result hints the enantioselective carrier protein affinity may be a key factor for stereoselective 1 m -PFOS transplacental transfer. The percentage of branched PFOS (% br -PFOS) and EF1 m -PFOS was correlated in maternal sera, but not in cord sera and placentas. These data indicated that % br -PFOS and EF1 m -PFOS may be less reliable in identifying PreFOS exposure when it comes to complex biological processes, such as transplacental transport. This study could expand our understanding of stereoselective placental contaminant transfer in humans. Graphical abstract: Image 1 Highlights: Chiral 1 m -PFOS was nonracemic in maternal serum, cord serum and placenta from mother-infant pairs in Wuhan. Chiral 1 m -PFOS was enantioselective during transplacental transfer in human. Molecular docking showed that two 1 m -PFOS enantiomers had enantioselective interactions with human serum albumin HSA. The enantiomer fraction of 1 m -PFOS was inversely correlated with percent branched PFOS in maternal sera. Percentages of branched PFOS may not be effective biomarkers of exposure.